2004
DOI: 10.1111/j.1464-5491.2004.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute brain injury in hypoglycaemia‐induced hemiplegia

Abstract: This report provides evidence that acute brain injury may be a cause of the neurological deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…17 Some authors have reported DWI and ADC findings of HE. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16]18 According to previous reports, the lesions show reversible cytotoxic edema at the cerebral cortex, 14,15,18 hippocampus, 19 splenium, 7,11,12,16 IC, 13,16 and cerebral WM. 5,8 These diffusion alterations are encountered not only in acute ischemia but also in hypoglycemia itself, and in vivo animal model studies have demonstrated diffusion alterations due to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Some authors have reported DWI and ADC findings of HE. [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16]18 According to previous reports, the lesions show reversible cytotoxic edema at the cerebral cortex, 14,15,18 hippocampus, 19 splenium, 7,11,12,16 IC, 13,16 and cerebral WM. 5,8 These diffusion alterations are encountered not only in acute ischemia but also in hypoglycemia itself, and in vivo animal model studies have demonstrated diffusion alterations due to hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…15 Hypoglycemia can cause various neurologic symptoms including profound memory loss, transient motor deficits, a persistent vegetative state, and death in 2%-4% of cases. [1][2][3]13 Brain MR imaging is a useful technique to evaluate severe HE. Among other sequences, DWI is a special technique that can measure the alteration of the diffusion of water within the extracellular space and between intracellular and extracellular spaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion-weighted magnetic resonance (MR) imaging is a useful method to detect early brain injury in the acute stage of ischemia, but is less well known in hypoglycemia-induced hemiparesis. 1,2,5,13,17) We report a case of hypoglycemia manifesting as hemiparesis in which diffusionweighted MR imaging demonstrated completely reversible signal changes in both the splenium of the corpus callosum and the posterior limb of the left internal capsule in the course of recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, patients are in coma or with respiratory failure; in the clinical outcome, entire disappearance of clinical features and even death have been reported due to hypoglycemic encephalopathy, deep memory loss and persistent vegetative state 1,4,5 . Hemiparesis is a rare and/or under-diagnosed clinical manifestation of hypoglycemia 6,7 .…”
Section: Discussionmentioning
confidence: 99%